An Analytical Study of the Ruling of Scholars about Receiving Gifts from Sultans and Kings - Kattoua, Muhammad Turkey (Journal of Islamic and Religious Studies, 2023)
Islamic Sharia is highly concerned with the behavior of scholars. This is because they are the heirs of prophets, and therefore, they are supposed to be good examples for people. Islamic Sharia controls the relationship between scholars and the men of authority (kings, sultans, and rulers). Since the scholars of Islam represent Islamic heritage and sciences, Sharia is keen on keeping this heritage in its respected position and consequently keeping the scholars in their high-level position and their word respected and acceptable in the hearts of people. To achieve this goal, Islamic Sharia has a general reservation to scholars' receiving gifts from kings and rulers, so there has been a big debate about that. Men of Islamic Jurisprudence agree that scholars must refuse gifts from the men of authority, especially if they are unjust and have dirty money (Haram funds). However, if the kings are just, scholars still prefer to refrain from accepting their money. That is because keeping away from the kings' gifts and prizes is graceful and keeps a scholar in a high-level position and his word free. By doing so, Islamic scholars stay in their high position, unaffected by any influence from the men of authority, and Sharia keeps effective and unaffected.